2023
DOI: 10.1021/acsami.3c00965
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially Coated Wavy Nanowire Composite Transparent Electrode for Stretchable Solar Cells

Abstract: Recent advances in fabricating stretchable and transparent electrodes have led to various techniques for establishing next-generation form-factor optoelectronic devices. Wavy Ag nanowire networks with large curvature radii are promising platforms as stretchable and transparent electrodes due to their high electrical conductivity and stretchability even at very high transparency. However, there are disadvantages such as intrinsic nonregular conductivity, large surface roughness, and nanowire oxidation in air. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…[68], copyright 2019 American Chemical Society); (b) Photographic images of the stretchable organic solar cells and in situ stretching test (reprinted with permission from Ref. [69], copyright 2023 American Chemical Society); (c) The stable performance of the energy fabric under different strain (reprinted with permission from Ref. [70], copyright 2020 American Chemical Society); (d) Comparison of the relatively resistive output between film sensor and serpentine sensor (reprinted with permission from Ref.…”
Section: Assembling Of Smart Fabric-type Stretchable Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…[68], copyright 2019 American Chemical Society); (b) Photographic images of the stretchable organic solar cells and in situ stretching test (reprinted with permission from Ref. [69], copyright 2023 American Chemical Society); (c) The stable performance of the energy fabric under different strain (reprinted with permission from Ref. [70], copyright 2020 American Chemical Society); (d) Comparison of the relatively resistive output between film sensor and serpentine sensor (reprinted with permission from Ref.…”
Section: Assembling Of Smart Fabric-type Stretchable Devicesmentioning
confidence: 99%
“…Secondly, stretchable solar cells that possess the capability to withstand substantial strain and exhibit superior cyclic mechanical resilience pose significance for application in wearable and skin-interfaced electronics. Son et al [69] successfully demonstrated a stretchable solar cell that exhibited remarkable stretchability and stability, which had been fabricated by introducing conductive polymers and ionic liquids into an intricate network of wavy silver nanowires. Remarkably, it was found that the solar cells were able to retain 89% of their initial efficiency even under a tensile strain of 20% (Figure 4b).…”
Section: Assembling Of Smart Fabric-type Stretchable Devicesmentioning
confidence: 99%
“…The advancement of next-generation optoelectronic devices, such as wearable electronics, smart healthcare systems, soft robotics, energy sources, and implantable sensors, necessitates the seamless integration of stretchability, transparency, and lightweight properties to conformably adherent to the human and robotic bodies while ensuring reliable human–machine interaction. Stretchable transparent electrodes (STEs) constitute a crucial construction unit in these optoelectronic devices by establishing an interface for the sensing, reception, and transmission of biological and physical signals between humans and machines . In the context of intimate contact between devices and biological tissues during various activities in daily life, STEs must exhibit operational stability along with high conductivity and transparency, while maintaining minimal loss in electronic function under strains up to 60% or even exceeding 100%. …”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of flexible electronic devices and sensors in recent years, more and more flexible conductive materials have been developed, such as graphene, conductive polymers, and noble metal nanowires. Although noble metal is relatively more expensive, AuNWs have been widely applied due to the advantages of strong electrochemical stability, high oxidation resistance, and outstanding biocompatibility compared with other metal nanowires. There are various methods to prepare AuNWs, including ultrathin AuNWs prepared by the soft film plate method and gold alloy nanowires grown on other metal nanowires. Among these materials, ultrathin AuNWs , prepared by the soft template method are a vital type of nanoscale material, which can be utilized in various electronic devices, including optical devices, enhanced electrocatalytic properties, gas detection, etc. However, two significant defects limit their application in the field of wearable devices.…”
Section: Introductionmentioning
confidence: 99%